2015
DOI: 10.1016/j.theriogenology.2014.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Maternal endocrine adaptation throughout pregnancy to nutrient manipulation: Consequences for sexually dimorphic programming of thyroid hormones and development of their progeny

Abstract: Maternal nutrient restriction during critical windows of fetal development alters postnatal growth, often in a sexually dimorphic manner. Intrauterine growth restriction is frequently characterized by accelerated growth and increased adiposity in later life. Thyroid hormones are implicated as part of the mechanism involved in this scenario via their actions within the hypothalamic-pituitary-thyroid axis. We fed high (H = 240%) and low (L = 70%) levels of recommended daily crude protein intake during the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 47 publications
7
37
4
2
Order By: Relevance
“…The sexual dimorphism observed, such that the effect peri-conception protein restriction effect was greater in the male, supports our previous findings in beef cattle (Micke et al 2011(Micke et al , 2014. This suggests that the male embryo is more susceptible to early gestational intervention than the female, as seen in the in vitro embryo (Bermejo-Alvarez et al 2011), and that this effect continues until at least 98dpc.…”
Section: Sexual Dimorphismsupporting
confidence: 88%
“…The sexual dimorphism observed, such that the effect peri-conception protein restriction effect was greater in the male, supports our previous findings in beef cattle (Micke et al 2011(Micke et al , 2014. This suggests that the male embryo is more susceptible to early gestational intervention than the female, as seen in the in vitro embryo (Bermejo-Alvarez et al 2011), and that this effect continues until at least 98dpc.…”
Section: Sexual Dimorphismsupporting
confidence: 88%
“…This in utero effect was, however, not discernible in later gross measures such as birthweight or postnatal growth as previously reported in lambs (Kotsampasi et al 2009) or calves (Micke et al 2015) but effects upon postnatal reproductive development were evident: the LPeri diet decreased blood vessel area in the fetal testis. Moreover, seminiferous tubule number and percentage was increased, although this effect was not evident in the adult.…”
Section: Discussionsupporting
confidence: 65%
“…Micke et al (2015) reported that protein intake in the first and second trimesters has sexually dimorphic effects on progeny appetite and postnatal growth pathways and that this is associated with altered circulating thyroid hormone and leptin concentrations in the progeny. In contrast, no differences in food intake (at 26-30 months of age) were attributed to wide differences in prenatal growth and birthweight (Greenwood and Cafe 2007).…”
Section: Epigenetic Programming Of Appetite Regulationmentioning
confidence: 99%
“…In general, reducing calf birthweight by means of maternal dietary restriction does not reduce the incidence of dystocia or calf morbidity. This is due to both effects on maternal physiology (Micke et al 2015) and changes to the immune status of the calf and colostrum (McGee et al 2006). However, in a few studies cow nutrition has been linked to calf mortality (e.g.…”
Section: Animal Behaviour and Welfarementioning
confidence: 99%